Construction of optimal binary low-correlation zone sequence sets - LI Yu-bo; XU Cheng-qian (Tongxin xuebao)
Based on binary pseudorandom sequences with period 2m-1,A new construction of column sequence sets with period 2m+1-1 was presented.With these column sequence sets,one can get a new class of binary low-correlation zone（LCZ） sequence sets whose parameters can reach the Tang-Fan-Matsufuji bound.These LCZ sequence sets have larger set size,as a result,they can be used in quasi-synchronous（QS） CDMA systems to support more users.